Guest

If a b c are in HP,prove that a:(a-b) =(a+b):(a-b).

If a b c are in HP,prove that a:(a-b) =(a+b):(a-b). 

Grade:11

1 Answers

Saurabh Koranglekar
askIITians Faculty 10335 Points
3 years ago
Dear student

Please consider a = 0.5
b = 0.25
c = 0.125

Check for LHS and RHS

Kindly check the question and re-post with the correct condition

Regards

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free